1998
DOI: 10.1074/jbc.273.51.34134
|View full text |Cite
|
Sign up to set email alerts
|

A New Remote Subsite in Ribonuclease A

Abstract: The interaction between bovine pancreatic ribonuclease A (RNase A) and its RNA substrate extends beyond the scissile bond. Enzymic subsites interact with the bases and the phosphoryl groups of a bound substrate. We evaluated the four cationic residues closest to known subsites for their abilities to interact with a bound nucleic acid. Lys-37, Arg-39, Arg-85, and Lys-104 were replaced individually by an alanine residue, and the resulting enzymes were assayed as catalysts of poly-(cytidylic acid) (poly(C)) cleav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 27 publications
(25 reference statements)
2
57
0
Order By: Relevance
“…The RNase A detection method previously reported [3][4][5][6]26 was 0.5 pg RNase A and the the detection limit of this method is in good agreement with that previously reported. These results showed that RNase could be detected by the mRNA-immobilized electrode coupled with 1.…”
Section: Treatment Of Mrna-immobilized Electrode With Rnase Asupporting
confidence: 78%
See 3 more Smart Citations
“…The RNase A detection method previously reported [3][4][5][6]26 was 0.5 pg RNase A and the the detection limit of this method is in good agreement with that previously reported. These results showed that RNase could be detected by the mRNA-immobilized electrode coupled with 1.…”
Section: Treatment Of Mrna-immobilized Electrode With Rnase Asupporting
confidence: 78%
“…[20][21][22] The immobilization of mRNA on the electrode thus obtained was then conducted based on the fact that deoxyguanosine or deoxycytidine of DNA could react with NHS-activated carboxylic acid on the electrode. 20,21 Since the mRNA used in this experiment had a lot of guanosine and cytidine, 24 the mRNA was expected to be immobilized through a similar reaction. Poly(A) + RNA from mouse kidney as mRNA had an averaged length of 1 -2 kb, confirmed by an Agilent 2100 bioanalyzer (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, binding interactions between enzymes and substrates, both directly at the site of chemical transformation and with nonreacting portions of the substrate have been shown to contribute to catalysis (e.g., refs. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. The mechanisms by which these noncovalent interactions can assist catalysis have been widely discussed, as briefly described in the following two paragraphs.…”
mentioning
confidence: 99%